Comparing flexural behavior of cement-bonded fiberboard reinforced bagasse, pine and coconut coir - Hoang Van Phong; Nazhad, Mousa M.; Nguyen, Thi Kim Oanh; Shipin, Oleg V.; Bohez, Erik L.J.; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2013)
This thesis focus on evaluate effluences of fiber content to flexural behavior of cement-bonded fiberboard reinforced bagasses, pine and coconut coir.In this thesis the applications of wood and non- wood fibers are considered in creating the Cement FiberBoards (CFB). Three different fibers including bagasses, pine and coconut coir fibers,which are 2% and 4% fiber content were changed by the weight of Portland cement, these fibers were mixed with cement to product CFB. Furthermore, Silica fume affected on flexural strength of CFB has also been studied. The results of this thesis shown that the flexural strength of the CFBs depends on the type fibers such as length, width, physical and mechanical fibers.All groups that increasing fiber content from 2% up to 4% of cement weight, increasing max flexural strength. In addition, silica fume alsoimproved the flexural strength for groups which captained it.
A thesis proposal submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Pulp and Paper Technology
Thesis (M. Eng.) - Asian Institute of Technology, 2013
Keywords: Coir; Plant fiber industry